PENGEMBANGAN MEDIA MISTAR GESER PADA MATERI PERKALIAN BILANGAN CACAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD - Nurul Rodhiah; Nila Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this research was to develop sliding ruler media, assess the product's validity, and determine the improvement in student learning outcomes. Enhancing students' arithmetic skills and understanding of mathematics can be achieved by introducing appropriate teaching media and instructional tools to support learning objectives. This study was conducted using research and development methods with the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation. Data collection techniques included questionnaires and tests. The validation results from media experts showed a percentage of 89%, categorized as very good, while material experts' validation results were 92%, also categorized as very good. Student responses indicated a positive reaction with a percentage of 49%. The pre-test results revealed that only 31% of the 26 students met the minimum competency criteria (KKM), while 69% did not meet the KKM. However, the post-test results indicated that 99% of students passed the KKM. Based on the tests conducted, there was a significant improvement in student learning outcomes after using the developed sliding ruler media for multiplication of whole numbers in Grade III.